Pengembangan Modul Elektronik Pemrograman Berorientasi Objek untuk Siswa Kelas XI Rekayasa Perangkat Lunak dengan Model Four-D - Permani, Angkati; Priyanto, Priyanto (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2019)
This article aims to explain the feasibility of an electronic-based